Efficacy of Crestar® and its combination with Folligon® on post-partum anoestrus in buffalo - SINGH, ANAND; SAXENA, M S; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
The effect of Crest~ alone and in combination with Folligon"' was studied in 24 post-partum anoestrous buffaloes underfield conditions. In control group (n = 8) the self-recovery was observed only in one buffalo (12.5%) in 23.0 days. In buffaloestreated with Crest~(n = 8) the oestrous recovery was 87.5% (P < 0.01) in an average duration of2.142±0.508 days and in buffaloestreated with Crestar"' in combination with Folligon"' the oestrous 'recovery was 87.5% (P < 0.01) in an average duration of3.428±0.202 days indicating that both the treatments can be effectively used to induce oestrum in post-partum anoestrous buffaloes.
Keywords: Post-partum anoestrum; progestagens; Crestar; folligon